MODEL PAIKEM DALAM PEMBINAAN AKHLAK SISWA MIN MEDAN BARAT - Nora Sopiah (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2017)
Abstract: Learning is one part of determining whether or not good alumni produced in a school. Welldesignedand well-designed learning will surely produce competent alumni. One of the lessons currentlybeing developed in Indonesia is PAIKEM learning (Active, Innovative, Creative, Effective, and Joyful Learning),but in reality there are still many schools that have not been able to implement this model optimally.Researchers choose Madrasah Ibtidaiyah Negeri Medan West as a place of research because it saw MadrasahIbtidaiyah Negeri Medan West has implemented this model and see much progress gained. The design ofPAIKEM model implemented in West Medan State Junior High School gets better after partnering withUSAID (United State Agency for International Development) by implementing learning programs that arepacked in module form. PAIKEM model design (Active, Innovative, Creative, Effective, and Joyful Learning)West Medan can not only be used in the form of general lessons, but can also be used in the formation ofmorals. This is caused by implementing PAIKEM model design (Active, Innovative, Creative, Effective, andExciting Learning, students do not feel bored, do not feel bored in following learning because of boredom,boredom that often trigger students morality is not good.